An upbringing with substance-abusing parents: Experiences of parentification and dysfunctional communication - Tedgård, Eva; Råstam, Maria; Wirtberg, Ingegerd (Nordisk alkohol- & narkotikatidskrift : NAT, 2019)
Aim: To increase understanding of the consequences of growing up with substance-abusing parents, including how this can influence the experience of becoming a parent. Methods: In-depth interviews were conducted with 19 parents who had participated in an Infant and Toddler Psychiatry Unit intervention programme and who had experienced substance-abusing parents in their family of origin. Directed qualitative content analysis was used to analyse the data. Results: Analysis of the interview material revealed both a high incidence of parentification and a conspiracy of silence concerning the substance abuse that helped generate symptoms of cognitive dissonance in the children. As parents they experience a high degree of inadequacy, incompetence and stress. Conclusion: A majority of the children who had grown up with substance-abusing parents responded by taking a parenting role for themselves, their siblings and their parents. These children, often well-behaved and seemingly competent, need to be identified and offered support as they risk developing significant psychological and emotional difficulties that can extend into adulthood. They form an extra sensitive group who may need special support up to and including the time when they become parents themselves. This finding underlines the importance of further research on parenting among those who have grown up with abusive parents.